Request for electronic access to administrative court case files in the context of Art. 74a(1)(1) of the Act on Administrative Court Procedure (Discourse of Law and Administration, 2023)
The author analysed Art. 74a AACP which regulates the issue of electronic service ofletters in administrative court procedure in the context of a request for electronic access to case files.The conclusion of the paper is that the legislator made the use of electronic service fully dependenton the express and undoubted consent of a party. Electronic filing of a request for mere access to thecase file obligates the administrative court only to provide access to the case file in that form anddoes not authorise the administrative court to serve the party all correspondence electronically. If,after the case file has been made available in the electronic mode, further correspondence betweenthe administrative court and the party is to be conducted in this mode, then the party should filea separate request referred to in Art. 74a(1)(2) AACP, or the court should request their consent underArt. 74a(1)(3) AACP to use electronic means of service.
Keywords: administrative court procedure; electronic access to case files; electronic service of letters